THE ROLE OF STORYTELLING IN CULTURAL IDENTITY PRESERVATION IN NATHANIEL HAWTHORNE’S “YOUNG GOODMAN BROWN” - Mohammed, Zakiuddin; Jesudas, Roseline (English Education Department of STKIP Pasundan, 2025)
This study examines the role of storytelling in preserving cultural identity, using Nathaniel Hawthorne’s